Rekultywacja i rewitalizacja gruntów pogórniczych na przykładzie gminy Kleczew = Reclamation and revitalization of post-mining land on the example of Kleczew - Gilewska, Mirosława; Otremba, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Kleczew commune is located in the eastern part of Wielkopolska in the district of Konin. In the municipality since 1965 is conducted lignite mining by KWB "Konin", now PAK KWB Konin SA On the surface about 2 000 ha (18% of the municipalities) was formed new sculpture area, including the highest point in the village (+129 m a.s.l.) called the Hill Kleczew. New soil cover is a conglomerate found in the overburden tills, mainly glacial boulder clay Warta, Quaternary sands, clays occasionally Pliocene.
Keywords: eksploatacja; rzeźba powierzchni; rekultywacja rekreacyjna; wtórna degradacja; opencast use; sculpture of area; recreational reclamation; secondary degradation